Stefano Ercolino e Massimo Fusillo, «Empatia negativa. Il punto di vista del male», Bompiani, 2022: Book review and interview with the authors (Balthazar, 2023)
Review of the volume «Empatia negativa. Il punto di vista del male» (Bompiani, 2022) and interview with authors Stefano Ercolino and Massimo Fusillo.